Doping - Garant nepotoplyaemosti teorii sportivnoi trenirovki - Yakimov, A. M. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
This article is concerned on the problems of long distance runners training. Author analyzed the record tables and noted that runners from highland countries (Ethiopia, Kenya, Mexico) many times beat ones from flat countries (Finland, USA, Great Britain). On the base of the records analysis, authoritative hypoxia researches and own training experience in mountains author defined six principles of highland training. Beside that, special weekly cycles of training in highland were elaborated. Author shares the views of several researchers (Y. Verchoshansky, V. Seluyanov and others) to the theory of sport training. As he noted, the TST cut the development of domestic sport science.